Correlation analysis of serum Fractalkine and AHO3 levels with the prognosis of acute cerebral infarction patients after intravenous thrombolysis: Serum Fractalkine and AHO3 levels in prognosis of ACI - Yun, Dong; Wang, Yu; Zuo, Peng; Deng, Shuai; Yan, Fangfang; Jin, Chai; Wang, Zhou (Journal of Medical Biochemistry, 2026)
Objective To examine the association between the prognosis of patients with acute cerebral infarction (ACI) following intravenous thrombolysis and the levels of blood AHO3 and Fractalkine. Methods A total of 322 patients with acute cerebral infarction (ACI) who underwent intravenous thrombolysis at this hospital from May 2023 to May 2025 were selected as research subjects. Based on the National Institutes of Health Stroke Scale (NIHSS) score at admission, the patients were classified into three groups: severe, moderate, and mild. Using the modified Rankin scale, the patients’ prognosis was assessed throughout a 90-day follow-up period. There were two groups of patients: those with a fair prognosis and those with a poor prognosis. Patients with varying degrees of illness severity had their serum levels of AHO3 and Fractalkine compared. The relationship between the severity of ACI and the levels of serum AHO3 and Fractalkine was examined using Spearman correlation analysis. The factors predicting poor prognosis following intravenous thrombolysis in ACI patients were examined using multivariate logistic regression, and the clinical data of the groups with excellent and poor prognoses were compared. Serum levels of AHO3 and Fractalkine alone and together were analyzed using a receiver operating characteristic (ROC) curve to predict poor outcome in patients with ACI following intravenous thrombolysis. Results There were 174 patients in the mild group, 102 patients in the intermediate group, and 46 patients in the severe group. The moderate group’s serum AHO3 level was lower than the mild group’s (P<0.010), while the severe group’s serum AHO3 level was lower than both groups’ (P<0.010). The moderate group had a higher serum Fractalkine level than the mild group, and the severe group had a higher serum Fractalkine level than the moderate and mild groups (P<0.010). The degree of ACI in patients was positively connected with the blood Fractalkine level (rs = 0.594, P = 0.001) and negatively connected with the serum AHO3 level (rs = -0.528, P = 0.007). A lower serum AHO3 level was found in the prognosis poor group compared to the prognosis good group (P<0.05). Furthermore, the serum Fractalkine level and admission NIHSS score of the prognosis poor group were greater than those of the prognosis excellent group, and their age was higher (P<0.05). ACI patients’ poor prognosis after intravenous thrombolysis was observed to be independently associated with older age, higher admission NIHSS score, and elevated serum Fractalkine level (P<0.05), while elevated serum AHO3 level was found to be an independent protective factor for poor prognosis following intravenous thrombolysis in ACI patients (P<0.05), according to multivariate logistic regression analysis. When age and admission NIHSS score were taken into account, multivariate logistic regression analysis revealed that elevated serum AHO3 levels continued to be an independent protective factor for poor prognosis after intravenous thrombolysis in ACI patients (P<0.05) and elevated serum Fractalkine levels continued to be an independent risk factor for poor prognosis after intravenous thrombolysis in ACI patients (P<0.05). In patients with ACI, the prediction areas under the curve (AUCs) for serum AHO3, Fractalkine, and their combination for predicting a poor prognosis following intravenous thrombolysis were 0.799, 0.792, and 0.900, respectively, according to the results of the ROC curve study. The combined prediction AUC outperformed the individual prediction AUCs of Fractalkine (Z = 2.799, P = 0.027) and AHO3 (Z = 2.129, P = 0.034). Conclusion The degree of ACI in patients is directly correlated with their serum levels of Fractalkine and AHO3. Following intravenous thrombolysis, individuals with ACI can have their prognosis evaluated using both of these signs, and their combination has a higher predictive value.